Synthesis of uniformly dispersed large area polymer/AgNPs thin film at air−liquid interface for electronic application - Mishra, R.; Pandey, R.K.; Jana, S.; Upadhyay, C.; Prakash, R. (Elsevier Ltd, 2020)
Owing to self-organizing properties of conjugated polymers (CPs) into ordered macroscopic structures, their π−π stacking (ordering) and thus electrical property are greatly influenced by intermolecular interactions when incorporated with another nanomaterial. Here, a molecular engineering technique is employed to enhance the ordering of polymer named “polyindole (PIn)” at air−water interface in the presence of silver nanoparticles (AgNPs). Comparative microscopic, macroscopic surface analysis and spectral analysis of Ag−PIn nanohybridand pristine PIn Langmuir films reveal a better molecular packing (π−π stacking) and oriented film structure for the former due to silver incorporation. Enhancement in ordering is attributed to the cooperative effort of the self-assembling property of AgNP and the Langmuir technique. Surface-enhanced Raman Spectroscopy (SERS) and XPS clearly support the formation of polymer−metal nanoparticle coupled unified system, via chemi-adsorption thus attributing to enhancement observed in intrinsic mobility (charge transport properties) of nanohybrid film. This work demonstrating the Langmuir and nanoparticle-induced ordering in polymer backbone will motivate the utilization of this technique for ordering and electronic property enhancement of other nanomaterial−polymer systems. © 2020 Elsevier Ltd
Keywords: Air-water interface; Floating film; π-π stacking; Polyindole; Silver nanoparticles